(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Purine and pyrimidine metabolism represents one of the most essential and tightly regulated biochemical pathways in living organisms, as it ensures the balanced synthesis and degradation of nucleotides required for cellular growth, differentiation, and genetic stability. These two types of nitrogenous bases are fundamental building blocks of nucleic acids — DNA and RNA — and play crucial roles in numerous cellular processes including energy transfer (ATP, GTP), signal transduction (cAMP, cGMP), enzymatic reactions, and coenzyme formation (NAD⁺, FAD, CoA).